The Physiological Role of Mitophagy: New Insights into Phosphorylation Events - Yuko Hirota; Dongchon Kang; Tomotake Kanki (International Journal of Cell Biology)
Mitochondria play an essential role in oxidative phosphorylation, fatty acid oxidation, and the regulation of apoptosis. However, this organelle also produces reactive oxygen species (ROS) that continually inflict oxidative damage on mitochondrial DNA, proteins, and lipids, which causes further production of ROS. To oppose this oxidative stress, mitochondria possess quality control systems that include antioxidant enzymes and the repair or degradation of damaged mitochondrial DNA and proteins. If the oxidative stress exceeds the capacity of the mitochondrial quality control system, it seems that autophagy degrades the damaged mitochondria to maintain cellular homeostasis. Indeed, recent evidence from yeast to mammals indicates that the autophagy-dependent degradation of mitochondria (mitophagy) contributes to eliminate dysfunctional, aged, or excess mitochondria. In this paper, we describe the molecular processes and regulatory mechanisms of mitophagy in yeast and mammalian cells.